Brucella Dysregulates Monocytes and Inhibits Macrophage Polarization through LC3-Dependent Autophagy - Wang, Yang; Li, Yuxiang; Li, Haijun; Song, Hongxiao; Zhai, Naicui; Lou, Lixin; Wang, Feng; Zhang, Kaiyu; Bao, Wanguo; Jin, Xia; Su, Lishan; Tu, Zhengkun (Frontiers in Immunology, 2017)
Brucellosis is caused by infection with Brucella species and exhibits diverse clinical manifestations in infected humans. Monocytes and macrophages are not only the first line of defense against Brucella infection but also a main reservoir for Brucella. In the present study, we examined the effects of Brucella infection on human peripheral monocytes and monocyte-derived polarized macrophages. We showed that Brucella infection led to an increase in the proportion of CD14++CD16− monocytes and the expression of the autophagy-related protein LC3B, and the effects of Brucella-induced monocytes are inhibited after 6 weeks of antibiotic treatment. Additionally, the production of IL-1β, IL-6, IL-10, and TNF-α from monocytes in patients with brucellosis was suppressed through the LC3-dependent autophagy pathway during Brucella infection. Moreover, Brucella infection inhibited macrophage polarization. Consistently, the addition of 3-MA, an inhibitor of LC3-related autophagy, partially restored macrophage polarization. Intriguingly, we also found that the upregulation of LC3B expression by rapamycin and heat-killed Brucella in vitro inhibits M2 macrophage polarization, which can be reversed partially by 3-MA. Taken together, these findings reveal that Brucella dysregulates monocyte and macrophage polarization through LC3-dependent autophagy. Thus, targeting this pathway may lead to the development of new therapeutics against Brucellosis.